PERENCANAAN STRATEGIS SUMBER DAYA MANUSIA DI BIDANG AKADEMIK - Desimarnis Desimarnis (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The strategic plan guides the school is successfully fulfilling its mission. Based on the strategic plan, the school can develop a human resource plan that allows it to make management decisions in the present to support the school's future direction. The general objective of human resource management is to ensure the organization has adequate human resources to meet its needs. Operational purposes and plans Allow the organization to stay informed of current social, economic, legislative and technological trends affecting human resources and Allows the organization to be flexible for dynamic changes in the environment. Human resource management identifying future needs with the school and developing scenarios about the future distinguishes human resource management from operational planning. The fundamental question that must be answered for strategic human resource management is? Where are we going? Given the circumstances, how are we going to get there? This article seeks to provide a framework for the strategic planning of human resources in academia.